(untitled) (International Journal of Engineering and Computer Science, 2014)
Digital medical imaging is highly expensive and complex due to the requirement of proprietary software and expert personnel. This paper introduces a user friendly general and visualization program specially designed in software called MATLAB for detection of brain disorder called Alzheimer’s disease as early as possible. This application will provide quantitative and clinical analysis of digital medical images i.e. MRI scans of brain. Very tiny and minute structural difference of brain may gradually & slowly results in major disorder of brain which may cause Alzheimer’s disease. Here the primary focus is given for detection & diagnosis of Alzheimer’s disease which will be implemented by using bi-cubic interpolation technique.